Validation of Comparative Model of the Teacher Education Systems - Mehri Ezazi; Mohammad Nourian; Ali akbar Khosravi Babadi; Darush Noroozi (Comparative Education Society of Iran ( CESIR), 2020)
The present study aimed to validate the comparative model of teacher education systems. For this quantitative study, correlation method and path analysis test were used in line with research purposes. The statistical population was faculty members of Farhangian University, Iran. The cluster sampling method was used to determine the sample size, and 250 faculty members from all over the country were selected as the study sample. A researcher made questionnaire including 50 items designed based on the components of the comparative model of the teacher education system was used to collect the data. Moreover, the exploratory factor analysis test was used to investigate the reliability of the instrument, employing the Principal Components Analysis (PC). The results showed that 7 factors had been identified according to the eigenvalues. The results of the explained variance showed that these 7 factors predicted a total of 70% of the structural changes. Then, in order to test the theoretical model, the proposed conceptual model analyzed by path analysis, employing the maximum probability method. After testing the model with fit indices, it was shown that the tested model enjoyed a good fit with the conceptual model and the collected data. In the end, suggestions were made, including that researchers and those involved in teacher education systems all over the world can use this model as a conceptual framework in their comparative approach in order to benefit from successful methods of teacher education.